HIV voluntary testing and perceived risk among female sex workers in the Mekong Delta region of Vietnam - Bach Xuan Tran; Long Thanh Nguyen; Nhung Phuong Nguyen; Huong Thu Thi Phan (Taylor & Francis Group, 2013)
Introduction: HIV voluntary counseling and testing (VCT) comprise an effective preventive measure and an entry point to care and support services. We sought to assess VCT uptake and HIV-related knowledge and perceived risk among female sex workers (FSWs) in five provinces of the Mekong Delta region. Methods: A cross-sectional survey was carried out in 1998 FSWs, including both street-based sex workers (SSWs) and entertainment-based sex workers (ESWs). Results: High proportions of FSWs were aware that using condoms (94.6%), and clean needles (34.1%) are preventive measures that reduce the risk of HIV transmission. Some FSWs reported avoiding public toilet use (8.6%), physical contacts (16.1%), or sharing meals (10.9%) with people living with HIV/AIDS, and preventing mosquito bites (20.8%). Twenty-nine percent (29.0%) of FSWs perceived themselves as being at risk of HIV infection. Only 32.7% had ever tested for HIV, of whom 54% were voluntary for testing. FSWs who ever injected drugs (OR = 0.03, p=0.05), had drug-injecting clients (OR = 0.07, p<0.01), and had inconsistent condom use with husbands or lovers (OR = 0.10, p=0.01) were less likely to have a voluntary test. Inconsistent condom use with clients (OR = 13.86, p<0.01), and receiving HIV information from radio (OR = 13.28, p<0.05) and communication campaigns (OR = 6.69, p<0.05), increased the likelihood of VCT uptake. Conclusion: Inadequate knowledge and some misconceptions about HIV transmission routes and preventive measures, low perceived risk of HIV infection, and low VCT uptake were observed among FSWs in the Mekong Delta region. Interventions to improve their knowledge and self-efficacy, reduce risky behaviors, and encourage VCT uptake and early access to health care services are necessary to prevent HIV transmission in this region.